Access to Justice as a Social Determinant of Health: The Basis for Reducing Health Disparity and Advancing Health Equity of Marginalized Communities - Jassar, Sunam (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2021)
Health disparity in Canada is continuing to grow with marginalized communities being disproportionately affected. Policies and actions implemented by the federal government have been ineffective in addressing underlying causes of poor health. Framing access to justice as a social determinant of health is a necessary first step to establish a comprehensive and interdisciplinary approach to address poor health outcomes.  Through an analysis of the limitations of access to justice as a legal term and the application of access to justice in health outcomes, this article hopes to foster further collaboration between the medical and legal communities in this area. art I of this paper argues the need to expand the scope of access to justice beyond the legal realm. Part II highlights the increasing health disparity within Canada and critiques the current approach. Part III outlines the ways in which health disparity can be improved if access to justice is recognized as a social determinant of health.  The paper concludes with discussing progress that can be made in both the legal and medical community as a result of widening the scope of access to justice. Through an analysis of the limitations of access to justice as a legal term and the application of access to justice in health outcomes, this paper hopes to foster further collaboration between the medical and legal communities in this area.